Effect of Students selected Context-Based Approach on Students’ Performance in Genetics (Journal of Educational Development and Practice, 2023)
The quest to maximize students' learning in the sciences has been on high alert in the recent past. This has brought into focus how teachers enact the content prescribed by the curriculum. Various approaches have been suggested as probable solutions to cure students' weak learning attainment in the sciences. One approach gaining grounds in the literature as a means of effectively teaching science concepts leading to the maximization of students' learning is context-based teaching. This research sought to explore the effectiveness of student-selected context-based teaching approaches on students' achievement in genetics concepts in Ghanaian senior high schools. Using 107 biology students from three schools, pretest-posttest non-equivalent group design was used to identify which of the student-selected context-based teaching was effective in improving learning outcomes in genetics.  Results indicate that the recent approach of students’ selected context-based teaching was more effective in improving the performance of students in genetics as compared to the modern and traditional approaches with a large effect size. It is recommended that biology instructors who use students' selected context-based approach to teach genetics should use the recent approach to context-based teaching, which has been demonstrated to be more successful in increasing students' genetics performance.
Keywords: Students’ selected context-based, recent approach, modern approach, traditional approach